On Weighted Stolarsky Means - Simić, Slavko (Sarajevo Journal of Mathematics, 2024)
In this article we study a weighted variant of the well known Stolarsky means. Its advantage is the possibility of a simple and natural extension to the multi-variable case. We also investigate some common properties of those classes of means. 2000 Mathematics Subject Classification. 26A51, 60E15